EXISTENTIAL ALIENATION AND ITS RELATIONSHIP TO THE LEVEL OF OPTIMISM AMONG - Hasan, Shahzad; Galety, Mohammad Gouse (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Abstract The research aimed to identify the level of existential alienation and optimism among Private university students and the relationship between the scores of the research sample on the existential alienation scale and their scores on the optimism scale. It also aimed at revealing the significance of the differences among the scores of the research sample on the optimism scale between students with high existential alienation and students with low existential alienation and measuring the significance of the differences among the research sample individuals on the existential alienation scale and the optimism scale according to the two research variables: (the academic year, and the economic level of the family). The researcher used the descriptive analytical approach. The research sample consisted of (301) male and female students from Lebanese French University. The optimism scale prepared by Abdul Khaleq was applied. The results showed:1. According to the existential alienation measure, the level of existential alienation among the research sample was high, and the level of optimism among the research sample was medium.2. There was a statistically significant negative correlation between the scores on the existential self-alienation scale and the optimism scale of the people in the study sample.3. Existential isolation among college students can be used to figure out how optimistic they are.4. There were statistically significant differences between the mean scores of the research sample’s answers on the scale of existential alienation based on the school year, which favoured students in their first year, and based on the family’s economic level, which selected students from poor families.5. There were statistically significant differences between the mean scores of the research sample’s responses on the optimism scale based on the academic year in favour of students in their fourth academic year and based on the family’s economic level in favour of students whose family’s economic level was good.